A comparative review on symmetric and asymmetric DNA-based cryptography - Baraa Tareq Hammad; Ali Maki Sagheer; Ismail Taha Ahmed; Norziana Jamil (Institute of Advanced Engineering and Science, 2020)
Current researchers have focused on DNA-based cryptography, in fact, DNA or deoxyribonucleic acid, has been applied in cryptography for performing computation as well as storing and transmitting information. In the present work, we made use of DNA in cryptographic, i.e. its storing capabilities (superior information density) and parallelism, in order to improve other classical cryptographic algorithms. Data encryption is made possible via DNA sequences. In this paper, two cases utilizing different DNA properties were studied by combining the DNA codes with those conventional cryptography algorithms. The first case concerned on symmetric cryptography that involved DNA coding with OTP (one time pad) algorithms. Asymmetric cryptography was considered in the second case by incorporating the DNA codes in RSA algorithm. The efficiencies of DNA coding in OTP, RSA, and other algorithms were given. As observed, the computational time of RSA algorithm combined with DNA coding was longer. In order to alleviate this problem, data redundancy was reduced by activating the GZIP compressed algorithm. The present experimental results showed that DNA symmetric cryptography worked quite well in both time and size analyses. Nevertheless, it was less efficient than the compressed DNA asymmetric cryptography.